INTENSITAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY: PENGUJIAN DENGAN MANAJEMEN LABA AKRUAL DAN RIIL - Setyastrini, Putri; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2017)
This research aims to get empirical evidence about the influence of accrual and real earning management on corporate social responsibility disclosure intensity. The study held at winners of Indonesia Sustainability Reporting Award in 2014-2015. Accrual earning management measured by discretionary accrual Kothari model (2005). For real earning management measured by Roychowdhury model (2006) with abnormal cash flow from operation and abnormal discretionary expenses approachment. CSR disclosure measured with GRI G4 Sustainability Reporting Guidelines. Data analyzed by multiple regressions linear analysis. Sample selected with non probability sampling method with purposive technique. The result showed accrual earning management has no impact to CSR disclosure, on the other hand real earning management has positive impact to CSR disclosure. It means CSR disclosure become an entrenchment strategy to hide real earning management that was done by corporate.
Keywords: corporate social responsibility, accrual earning management, real earning management